Qualitative evaluation of a deferred consent process in paediatric emergency research: a PREDICT study. Issue 11 (15th November 2017) - Furyk, Jeremy; McBain-Rigg, Kristin; Watt, Kerrianne; Emeto, Theophilus I; Franklin, Richard C; Franklin, Donna; Schibler, Andreas; Dalziel, Stuart R; Babl, Franz E; Wilson, Catherine; Phillips, Natalie; Ray, Robin
Abstract : Background: A challenge of conducting research in critically ill children is that the therapeutic window for the intervention may be too short to seek informed consent prior to enrolment. In specific circumstances, most international ethical guidelines allow for children to be enrolled in research with informed consent obtained later, termed deferred consent (DC) or retrospective consent. There is a paucity of data on the attitudes of parents to this method of enrolment in paediatric emergency research. Objectives: To explore the attitudes of parents to the concept of DC and to expand the knowledge of the limitations to informed consent and DC in these situations. Method: Children presenting with uncomplicated febrile seizures or bronchiolitis were identified from three separate hospital emergency department databases. Parents were invited to participate in a semistructured telephone interview exploring themes of limitations of prospective informed consent, acceptability of the DC process and the most appropriate time to seek DC. Transcripts underwent inductive thematic analysis with intercoder agreement, using Nvivo 11 software. Results: A total of 39 interviews were conducted. Participants comprehended the limitations of informed consent under emergency circumstances and were generally supportive of DC. However, they frequently confused concepts of clinical care and research, and support for participation was commonly linked to their belief of personal benefit. Conclusion: Participants acknowledged the requirement for alternatives to prospective informed consent in emergency research, and were supportive of the concept of DC. Our results suggest that current research practice seems to align with community expectations.